Permanence of the effect provided by auditory training in subjects with auditory processing disorder - Stella Medianeira Soares Quinto; Lidiéli Dalla Costa; Bianca Bertuo; Sheila Jacques Oppitz; Michele Vargas Garcia; Eliara Pinto Vieira Biaggio (O Mundo da Saúde, 2017)
The objective was to verify the permanence of the effect provided by auditory training in subjects with auditory processing disorder, within 30 days after the intervention and after 10 months. This was a retrospective, longitudinal, and descriptive study, with three subjects (10 to 27 years old) evaluated through the Compressed Speech Test and the Staggered Spondaic Words (SSW) Test before and after an Acoustically Controlled Auditory Training Program. The subjects were treated at a School of Speech Therapy clinic. All ethical issues were respected. The data analysis was performed in a descriptive way. For pre- and post-training analysis, we verified that the Compressed Speech and the Staggered Spondaic Words Tests were in Portuguese. One subject underwent auditory training with the use of software and two others were rehabilitated through training in a sound-treated booth. The results of the re-evaluation after 30 days and after 10 months remained the same without prejudice of time. All subjects had improved trained auditory skills, according to the increase of the percentage of correct answers for the two behavioral tests applied. We concluded that there was the permanence of the training’s effect on auditory processing abilities after 10 months of intervention, which shows the effectiveness of the proposed Acoustically Controlled Auditory Training, even with the passage of time.